Relationship Between CVMI and Dental Calcification Stages - Anushri Bhardwaj; Sheron Bhanat; Mahishi G. Suthar; Shatha Ahmad Mohammad Jafari; Shreya Daga; Manoj Meena; Akshaya Ojha (Journal of Pharmacy and Bioallied Sciences)
Background: Assessment of skeletal and dental maturation (DM) is a commonly applied approach in dental practice for growth modification. The main objective of the study is to find the relationship between the cervical vertebral maturation index (CVMI) and dental calcification stages. Methodology: A total of 85 patients were selected for the study. Patients aged between 8 and 16 years, as this is a period of active growth and development where both skeletal and DM can be observed were included in the study. Results: CVMI stages show that most patients were in the active growth phases, with the highest percentage (24%) in Stage 3 (pubertal growth spurt), indicating a period of rapid skeletal development. Stage 4 (post-pubertal stage) accounted for 21% of the patients, while 18% were in Stage 2 (initial pubertal growth). Patients in Stage 5 (late-stage growth) and Stage 6 (completion of skeletal growth) made up 14% and 12%, respectively, reflecting near or fully completed skeletal development. Additionally, 12% of patients were in Stage 1 (pre-pubertal growth), indicating minimal skeletal development at the time of assessment. Conclusion: It is concluded that there is a strong positive correlation between CVMI and dental calcification stages, making both reliable indicators of growth and development.